Cotton biotechnology: An efficient gene transfer protocol via agrobacterium tumefaciens for a greater transgenic recovery - ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
Due to its economic worth, cotton (Gossypium hirsutum L.) is grown in almost 70 countries and provides income for more than 250 million people. Therefore, producing cotton with having some desired characteristics that includes extended biotic and abiotic stress tolerance, improved fiber quality, promoted nutritional content and increased yield is the main objective for cotton biotechnology. To achieve this goal, many tissue culture and gene transfer techniques are being developed and used throughout the years. As applications for the gene transfer, the Agrobacterium-mediated, particle bombardment and pollen tube pathway-mediated methods are most successfully used and in conjunction with this, meristematic shoot tips as explants are efficiently utilized in gene transfer methods. In this study, the main objective was to report an efficient protocol for a greater recovery of transgenic cotton plant using Agrobacterium tumefaciens-mediated transformation. For this, one of the cotton strains (Cukurova 1518) cultivated widely in Turkey was chosen and meristematic shoot tips as explant sources, and GFP and NPTII genes as reporter and marker genes were used, respectively. The effective post co-cultivation conditions were provided via using the selection regime in vitro. Finally, the current results showed highly reproducible protocol developed could be used to produce transgenic cotton plants expressing desired traits or can be utilized as a model system to study the expression of particular genes.

由于其经济价值, 棉花 (Gossypium hirsutum L.) 在近70个国家种植, 为2.5亿 多人提供收入. 因此, 棉花生物技术的主要目标是生产具有某些期望特性的 棉花, 包括延长生物和非生物胁迫耐受性、改善纤维品质、提高营养含量 和增加产量. 为了实现这一目标, 多年来, 许多组织培养和基因转移技术被 开发和使用. 作为基因转移的应用, 农杆菌介导、粒子轰击和花粉管通道介 导的方法被最成功地使用, 与此相结合, 分生茎尖作为外植体被有效地用于 基因转移方法. 在这项研究中, 主要目的是报告一种利用根癌农杆菌介导的 转化更有效地恢复转基因棉花植株的方案. 为此, 选择在土耳其广泛种植的 棉花品系之- (Cukurova 1518), 分生茎尖作为外植体来源, GFP和NPTII基因分 别作为报告基因和标记基因. 通过体外筛选机制提供了有效的共培养后条 件. 最后, 目前的结果表明, 所开发的高重复性方案可用于生产表达所需性 状的转基因棉花植株, 或用作研究特定基因表达的模型系统.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); General Materials Science; Physical Sciences; Gossypium hirsutum L; gene transfer; meristematic shoot; blotting techniques; GOSSYPIUM-HIRSUTUM L.; PLANT-REGENERATION; SOMATIC EMBRYOGENESIS; ROOT-FORMATION; TRANSFORMATION; SHOOT; TISSUE; BARBADENSE; CULTIVARS; GENOTYPE; Gossypium hirsutumL; 基因转移; 分生芽; 印迹技 术; Gossypium hirsutum L.; gene transfer; meristematic shoot; blotting techniques